Memberdayakan Siswa SMA Menciptakan Usaha Mikro Berbasis Aplikasi Pesan-Instan dan Media Sosial - Angelica Salsyabila A,P; Hedrian Saputra; Muhamad Abyzar Ramadhan (Jurnal Ekonomi dan Bisnis Digital, 2026)
The rapid development of digital technology, with internet penetration in Indonesia reaching 64%, has created significant opportunities for the growth of the creative economy, particularly among the digital native generation at the high school level. This Community Service (PKM) activity aims to empower students at SMA Puspita Bangsa Ciputat to create micro-businesses based on instant messaging applications and social media to foster an independent and innovative entrepreneurial mindset. The implementation method was participatory, educational, and applied, involving visual material delivery, interactive discussions on real-world case studies such as "Zee Apps", and direct practical simulations including WhatsApp Business optimization and creative content production. Furthermore, the program introduced data-driven digital content innovation (basic analytics) using platform insight features and simple A/B testing to objectively evaluate marketing strategies . The results indicate high student enthusiasm and a shift in perception regarding social media as a strategic platform for micro-business marketing. Measurable impacts include a 3-fold increase in communication and time management soft skills, with 85% of students demonstrating readiness for economic independence. While challenges such as digital distractions and data security remain, the activity successfully fostered a productive school entrepreneurship ecosystem. It is recommended that schools integrate digital marketing training into the "Kurikulum Merdeka" and establish a "Digital Hub" or school business incubator to ensure a sustainable student micro-business ecosystem.digital marketing training into the "Kurikulum Merdeka" and strengthen the synergy between teachers and parents in digital literacy mentoring to ensure a sustainable and responsible student micro-business ecosystem